Recollections of the war with Mexico - Henshaw, John C., b. 1815 (University of Missouri Press, 2008)
"Major John Henshaw's firsthand account of the American invasion of Mexico includes not only narratives of the war's major battles but also forceful critiques of military leadership and strategies and vivid descriptions of Mexico's countryside, cities, and people. Editor Gary Kurutz provides extensive annotations of Henshaw's journals and letters"--Provided by publisher.